Pengaruh Pemberian Ekstrak Etanol Bit Merah (Beta vulgaris) terhadap Kerusakan Histologis Sel Ginjal Mencit (Mus musculus) yang Diinduksi Parasetamol - Amanda Yessica Anggara; . Muthmainah; Yulia Sari (Nexus Biomedika, 2013)
Background: Kidney failure can happen due to intoxication of paracetamol that causes oxidative stress. Red beet (Beta vulgaris) containing various components such as vitamin A, C and E, flavonoid, Cu, Zn, Mn, selenium, betanin, and phenolic has a function as antioxidants. The aims of this research were to know the nefroprotective effect of ethanol extract of red beet to prevent renal cell damage of mice. Methods: This was laboratory experimental research with posttest only controlled group design. Subjects of this research were thirty Swiss webster male mice (Mus musculus), 2-3 months old and 20 grams of body weight (BW), each.. The subjects were divided into 5 groups randomly. The groups of this research were negative control (KK(-)), positive control (KK(+)), experimental group 1 (KP1), experimental group 2 (KP2), and experimental group 3 (KP3). The KP1, KP2 and KP3 were administered 5.6 mg, 11.2 mg and 22.4 mg per 20g BW, successively. The nefroprotective effect of ethanol extract of red beet to prevent renal cell damage of mice was assessed by counting the number of damage cells among 50 renal cells on pars convulata. Results: One-Way ANOVA analysis p=0.000 (p<0.05) followed by Post Hoc Multiple Comparisons showed a significant difference between negative control and other groups. The increasing dose of the ethanol extract of red beet was followed by the improvement of the protective effect. The linear regression test p=0.000 (p<0.05) showed a correlation between the increase of dose of ethanol extract of red beet and the improvement of the nefroprotective effect to the histological damage of mices renal cells. Conclusions: Ethanol extract of red beet showed the nefroprotective effect to the histological damage of mices renal cells induced by paracetamol. The increase of dose of the ethanol extract of red beet improved the protective effect to mices renal cells. Keywords: ethanol extract of red beet, histological damage of mices renal cells, paracetamol